Hierarchically Porous Polypyrrole Foams Contained Ordered Polypyrrole Nanowire Arrays for Multifunctional Electromagnetic Interference Shielding and Dynamic Infrared Stealth - Liu, Yu‑long; Zhu, Ting‑yu; Wang, Qin; Huang, Zi‑jie; Sun, De‑xiang; Yang, Jing‑hui; Qi, Xiao‑dong; Wang, Yong (Nano-Micro Letters, 2024)
As modern communication and detection technologies advance at a swift pace, multifunctional electromagnetic interference (EMI) shielding materials with active/positive infrared stealth, hydrophobicity, and electric-thermal conversion ability have received extensive attention. Meeting the aforesaid requirements simultaneously remains a huge challenge. In this research, the melamine foam (MF)/polypyrrole (PPy) nanowire arrays (MF@PPy) were fabricated via one-step electrochemical polymerization. The hierarchical MF@PPy foam was composed of three-dimensional PPy micro-skeleton and ordered PPy nanowire arrays. Due to the upwardly grown PPy nanowire arrays, the MF@PPy foam possessed good hydrophobicity ability with a water contact angle of 142.00° and outstanding stability under various harsh environments. Meanwhile, the MF@PPy foam showed excellent thermal insulation property on account of the low thermal conductivity and elongated ligament characteristic of PPy nanowire arrays. Furthermore, taking advantage of the high conductivity (128.2 S m−1), the MF@PPy foam exhibited rapid Joule heating under 3 V, resulting in dynamic infrared stealth and thermal camouflage effects. More importantly, the MF@PPy foam exhibited remarkable EMI shielding effectiveness values of 55.77 dB and 19,928.57 dB cm2 g−1. Strong EMI shielding was put down to the hierarchically porous PPy structure, which offered outstanding impedance matching, conduction loss, and multiple attenuations. This innovative approach provides significant insights to the development of advanced multifunctional EMI shielding foams by constructing PPy nanowire arrays, showing great applications in both military and civilian fields. Highlights: 1 Hierarchical melamine foam (MF)/polypyrrole (PPy) nanowire arrays (MF@PPy) were fabricated by electrochemical polymerization. 2 The 3D porous PPy micro-skeleton and the 1D PPy nanowire arrays imparted the MF@PPy foams with high electromagnetic interference shielding performance of 19,928.57 dB cm2 g−1 via multiple attenuations. 3 The PPy nanowire arrays achieved multifunctional integration including hydrophobicity, thermal insulation, and dynamic infrared thermal camouflage properties.